Comica as A Media for Increasing Language Skills in Class XII Students of SMAN 1 Telukjambe Karawang Academic Year 2021-2022 - Permata Yuliastuti; Euis Eti Rohaeti (JLER (Journal of Language Education Research), 2022)
ABSTRACTComic books as learning can be made using the Comica application downloaded on the play store and can be done through students' android phones, making it easier for students. Based on this, a research was conducted that aims to describe the learning process through the Comica medium of Indonesian language subjects with job application letter material and to find out student responses to the media at SMA Negeri 1 Telukjambe Barat. As an alternative learning media during the Covid-19 period, the Comica application can be used to train language skills (cognitive, affective, and psychomotor) properly and correctly. The method used is descriptive qualitative with verbal data. The research subjects were 23 students of class XII Mathematics and Natural Sciences 1 Academic Year 2021-2022. Data acquisition is done by observation and questionnaires. The results of this study resulted in learning in the form of comics and showed that Comica media in Indonesian language learning materials for job application letters was well received by students. ABSTRAKKomik sebagai pembelajaran dapat dibuat dengan menggunakan aplikasi Comica yang diunduh di play store dan dapat dilakukan melalui ponsel android siswa sehingga memudahkan siswa. Berdasarkan hal tersebut maka dilakukan penelitian yang bertujuan untuk mendeskripsikan proses pembelajaran melalui media Comica mata pelajaran bahasa Indonesia dengan materi surat lamaran kerja dan untuk mengetahui respon siswa terhadap media tersebut di SMA Negeri 1 Telukjambe Barat. Sebagai media pembelajaran alternatif di masa Covid-19, aplikasi Comica dapat digunakan untuk melatih kemampuan berbahasa (kognitif, afektif, dan psikomotorik) dengan baik dan benar. Metode yang digunakan adalah deskriptif kualitatif dengan data verbal. Subjek penelitian adalah 23 siswa kelas XII MIPA 1 Tahun Pelajaran 2021-2022. Perolehan data dilakukan dengan observasi dan angket. Hasil penelitian ini menghasilkan pembelajaran dalam bentuk komik dan menunjukkan bahwa media Comica pada materi pembelajaran bahasa Indonesia surat lamaran kerja diterima dengan baik oleh siswa. Responden menyatakan bahwa Comica dapat dengan mudah membantu meningkatkan kemampuan berbahasa.